2023
DOI: 10.1038/s41396-023-01500-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraspecific variation in insect microbiomes on host phenotype and evolution

Claudia Lange,
Stéphane Boyer,
T Martijn Bezemer
et al.

Abstract: Microbes can be an important source of phenotypic plasticity in insects. Insect physiology, behaviour, and ecology are influenced by individual variation in the microbial communities held within the insect gut, reproductive organs, bacteriome, and other tissues. It is becoming increasingly clear how important the insect microbiome is for insect fitness, expansion into novel ecological niches, and novel environments. These investigations have garnered heightened interest recently, yet a comprehensive understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…In contrast, pests, including bark beetles and their associated microbiota, can successfully invade host trees by compromising host defence (25). The insect microbiota is often influenced by the diet, sex, life stages, and the environment and facilitates the expansion of the ecological and evolutionary potential of their hosts (63,64). There has been growing interest in understanding the role of insect-microbial association in shaping the plasticity of insects in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pests, including bark beetles and their associated microbiota, can successfully invade host trees by compromising host defence (25). The insect microbiota is often influenced by the diet, sex, life stages, and the environment and facilitates the expansion of the ecological and evolutionary potential of their hosts (63,64). There has been growing interest in understanding the role of insect-microbial association in shaping the plasticity of insects in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that plasticity in insects can be mediated by associated microbes (Kolodny & Schulenburg, 2020). Variation in the microbial communities in host insects is high (Lange et al, 2023), and the microbial community can evolve, which can facilitate persistence in new and challenging environments (Kolodny & Schulenburg, 2020). Microbes, therefore, can serve as an important source of adaptive phenotypic plasticity (Kolodny & Schulenburg, 2020;Ghalambor et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Microbes, therefore, can serve as an important source of adaptive phenotypic plasticity (Kolodny & Schulenburg, 2020;Ghalambor et al, 2007). Insect-associated microbes can be transmitted from parent to offspring (Lange et al, 2023), indicating that plasticity could be multi-generational. If the microbial community influences fitness in the presence of deltamethrin, it is possible that plasticity and adaptation in the microbiome helped facilitate the observed increase in growth rate during the rescue experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascertaining how microbes influence host diversification first requires a better understanding of how microbial composition and function reflects intraspecific variation in hosts (e.g. morphological, genetic and geographical; Evans et al., 2021; Kelly et al., 2021; Lange et al., 2023).…”
Section: Introductionmentioning
confidence: 99%